PENGARUH PEMBERIAN PENGUATAN TERHADAP MOTIVASI BELAJAR SISWA DI SEKOLAH DASAR - Grasella, Nindya; Muhammadi, Muhammadi; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this research was to knowing effect of giving Reinforcement on student in Class IV . This research is a quantitative with type experimental research. Sampling data was collected with saturated sampling. The sample amounted to 40 people. Instrument that used to collecting data in this research is questionnaire test with a cheklist form. The result of research is that tcount> ttable, for motivation 4,7279 > 2,024 it means H0 is rejected  too. So that Ha accepted that there is effect the use of reinforcement on student motivation in Class IV primary School 13 Cingkariang Kabupaten Agam.Keyword: Reinforcement, Motivation to Learn, Learning